Scientific and Technical Translation: Contributions from Translation Studies - Franco Aixelá, Javier (2013)
Tradicionalmente, la traducción científico-técnica ha contado poco en la reflexión tanto lingüística como traductológica por partir de un lenguaje escasamente creativo. Hasta las últimas décadas del siglo XX los investigadores no comienzan a prestarle verdadera atención. En este trabajo se analizan las aportaciones de los estudios de traducción modernos a esta modalidad de transferencia interlingüística. La traductología se desarrolla a partir de una perspectiva textual y se vuelca sobre la optimización del texto meta, como un instrumento de comunicación semiautónomo que debe encajar en un nuevo sistema de expectativas y convenciones. Se presta atención a dos aspectos de la traducción: la interferencia y la posibilidad de mejora del texto original. Traditionally, scientific and technical translation has been given less importance in linguistic and translatological research because it uses a variety of language which is barely creative. Until the last decades of the 20th century, researchers had not given it real attention. The main contributions made by modern translation studies are analyzed in this paper. Translation studies takes a textual stance and focuses on optimizing the target text, which is understood as a semi-autonomous communication tool that must fit into a new system of expectations and conventions. Two other translation issues are also addressed here: interference and the possibility of improving the source text.